Can Expanding Contraceptive Access Reduce Adverse Infant Health Outcomes? - James Flynn (Institute of Labor Economics (IZA), 2024)
This paper uses the implementation of a privately funded family planning program in Colorado to demonstrate that expanding access to long-acting reversible contraceptives to lower income women creates positive selection in the health of the children being born, reducing the rates of extremely preterm births and infant mortality. My most conservative estimates suggest reductions of 1.1 extremely preterm births and 0.9 infant deaths per 1,000 live births, with the largest reduction in deaths due to Sudden Infant Death Syndrome. This suggests that expanding contraceptive access could help close the infant mortality gap between the U.S. and other leading economies.
Keywords: J13; I18; I12; 330; preterm birth; infant mortality; contraceptive access; family planning